2016
DOI: 10.1016/j.chroma.2015.12.087
|View full text |Cite
|
Sign up to set email alerts
|

A simultaneous derivatization of 3-monochloropropanediol and 1,3-dichloropropane with hexamethyldisilazane–trimethylsilyl trifluoromethanesulfonate at room temperature for efficient analysis of food sample analysis

Abstract: This paper reports the application of hexamethyldisilazane-trimethylsilyl trifluoromethanesulfonate (HMDS-TMSOTf) for the simultaneous silylation of 3-monochloro-1,2-propanediol (3-MCPD) and 1,3-dicholoropropanol (1,3-DCP) in solid and liquid food samples. 3-MCPD and 1,3-DCP are chloropropanols that have been established as Group 2B carcinogens in clinical testing. They can be found in heat-processed food, especially when an extended high-temperature treatment is required. However, the current AOAC detection m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Due to the potential carcinogenicity of 3-MCPD, many countries have set a maximum acceptable concentration of 3-MCPD at three levels: 0.02, 0.2, and 1.0 μg mL À1 . 4 It can be observed that the developed method can meet the real sample detection requirements.…”
Section: Methods Validationmentioning
confidence: 94%
See 3 more Smart Citations
“…Due to the potential carcinogenicity of 3-MCPD, many countries have set a maximum acceptable concentration of 3-MCPD at three levels: 0.02, 0.2, and 1.0 μg mL À1 . 4 It can be observed that the developed method can meet the real sample detection requirements.…”
Section: Methods Validationmentioning
confidence: 94%
“…A comparison with other derivatization techniques was performed to evaluate the performance of the developed method. 4,12,13,24,40 Compared with the traditional techniques such as HPLC and GC-MS, the proposed method has a relatively high sensitivity and a superiority in the analysis time, the sample pretreatment processes, and the requirement of the amount of foodstuffs (Table 2). Therefore, the developed method can be employed as a high-throughput strategy in real applications to screen samples with illegal amounts of 3-MCPD.…”
Section: Comparison With Other Techniquesmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, the low molecular weights of 3-MCPD and 1,3-DCP result in low m / z fragmentation patterns following mass spectrometer (MS) ionization. Derivatizing agents previously used in the simultaneous analysis of 3-MCPD and 1,3-DCP include N -methyl- N -(trimethylsilyl) trifluoroacetamide (MSTFA), bis­(trimethylsilyl) trifluoroacetamide (BSTFA), , heptafluorobutyric anhydride (HFBA), , heptafluorobutyrylimidazole (HFBI), , hexamethyldisilazine-trimethylsilyl trifluoromethanesulfonate (HDMS-TMSOTf), HFBA modified with trimethylamine (HFBA-Et 3 N), and 1-trimethylsilylimidazole (TSIM) . Phenylboronic acid (PBA) can be used to derivatize 3-MCPD but not 1,3-DCP because PBA needs two hydroxyl groups to form the cyclic phenyl boronate derivative .…”
Section: Introductionmentioning
confidence: 99%